The More Stringent, the Better? Rationing Car Use in Bogotá with Moderate and Drastic Restrictions - Bonilla, Jorge A. (Published by Oxford University Press on behalf of the World Bank, 2020)
Rationing car use based on license plate number has become a popular policy in several cities around the world to address traffic congestion and air pollution. This paper studies the effects of the moderate and drastic driving restrictions imposed as part of the Pico y Placa program on car use and air pollution in Bogotá. Using data on ambient carbon monoxide, gasoline consumption, and vehicle sales and registrations, no evidence of an improvement in air quality or a reduction in car use is found in either phase of the program. On the contrary, there is some indication that, relative to the moderate phase, gasoline consumption, vehicle ownership, and carbon monoxide in the morning peak tended to increase slightly when drastic restrictions were implemented.